SANOHENIC REFLECTION AS AN INTERNAL RESOURCE OF PERSONALITY - Ярош, Ніна Сергіївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article presents an analysis of the resource approach to the problem of coping behavior of the individual. The author examines the internal resources of the individual which are able to inﬂ uence the effectiveness and adaptability of coping strategies. The article raises the question of sanohenic reﬂ ection as a component of the internal resource of the individual. The results of the study of the inﬂ uence of training in the skills of sanohenic thinking are described. Correlations and signiﬁ cant differences are considered.